The Sociology of Religion Theoretical and comparative perspectives - Hamilton, Malcolm (Routledge, 2001)
This clear introduction to the sociology of religion combines a discussion of key theorists with a modern emphasis on the diversity of religious beliefs and practices. Malcolm Hamilton's expanded second edition brings the discussion fully up-to-date, and extends its material on secularization and religious sects, giving a broad comparative view. Drawing on the insights of history, anthropology and sociology, he surveys classic and contemporary theory to give a full picture of the variety and scope of theoretical perspectives.